Assessment of the degree of pollution of the middle reaches of the Dnipro River and development of measures to minimize it - Kasimov, Oleksandr; Udalov, Igor; Kononenko, Alina (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problems Statement and Purpose. Ukraine is currently facing technical and ecological and hygienic challenges to minimize pollution of surface and groundwater, a number of which, in relation to the Dnipro River basin, are discussed in this article. The authors of the article tried to characterize the problem of untreated wastewater and sludge reservoirs of industrial enterprises of Ukraine in two ways, since, on the one hand, they are man-made deposits of useful components of large-tonnage waste, and on the other hand, they cause serious harm to all components of the environment. The purpose of the study is to determine the degree of negative impact of wastewater and sludge storage tanks on the Dnipro River basin and to propose measures to improve water quality in the main source of water supply in the area where one of the largest metallurgical plants in Ukraine, Zaporizhstal, is located. Materials and Methods of Research. The work uses the methodology of integrated assessment of environmental quality to rank the territory of the sludge storage facility by the level of technogenic load and the degree of its impact on individual components of the environment. Results. The article assesses the impact of industrial wastewater and sludge storage tanks on the state of the Dnieper River water basin. Water quality monitoring was carried out in water bodies of the Dnipro River basin with the determination of the most common pollutants, including compounds of technogenic metal deposits (Mn, Cu, Zn, Fe, Pb ions), nitrogen compounds, and phenols. A schematic diagram of the entry of toxic compounds of heavy and rare metals from technogenic deposits into surface, groundwater and soil and their content in the soil near the wastewater and sludge storage tank is presented. A basic structural diagram has been developed for the sludge storage tank of the Zaporizhstal plant to minimize damage to the environment from its impact. The methodology of integrated assessment of environmental quality was used to rank the territory of the sludge storage facility of the Zaporizhstal plant by the level of technogenic load and the degree of this impact on individual components of the environment. The main measures for preventing and limiting damage to the environment are presented. Conclusions. 1. The problem of preventing damage to the environment in areas where untreated wastewater and sludge storage facilities of industrial enterprises of Ukraine are located is twofold: on the one hand, they are man-made deposits of useful components of large-tonnage waste, and on the other hand, they cause serious damage to all components of the natural environment. 2. The feasibility of investments in the utilization of valuable components from the composition of discharged wastewater and sludge is characterized by a large economic effect and a short payback period for the created production facilities. 4. The data provided by the statistics may be useful for forecasting the influx of excess wastewater into the natural medium from the side of accumulative wastewater, tailings and dumps of large-tonnage waste at other facilities.